2012
DOI: 10.1002/biof.201
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines, an adipose tissue and placental product with biological functions during pregnancy

Abstract: Latter half of pregnancy is characterized by a "physiological diabetogenic state" since changes in insulin-sensitivity have been well documented. These changes ensure continuous supply of nutrients to the growing fetus. In the last years the role of adipocyte-derived signaling molecules, collectively known as adipokines has been object of different in vitro and in vivo studies. Of interest, adipokines and/or their receptors are expressed in the placental tissue which, therefore, can contribute to development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 127 publications
(159 reference statements)
2
43
0
7
Order By: Relevance
“…34 It is hypothesized that maternal circulation of leptin is important for mobilization of fat deposits to ensure energy availability for the fetus. 35 Because measurement of plasma leptin in this study occurred within a narrow gestational timeframe (35-39 weeks), we do not believe differences in placental leptin production were responsible for the differences in leptin concentration seen between normal weight and overweight/obese pregnant women.…”
Section: Discussionmentioning
confidence: 80%
“…34 It is hypothesized that maternal circulation of leptin is important for mobilization of fat deposits to ensure energy availability for the fetus. 35 Because measurement of plasma leptin in this study occurred within a narrow gestational timeframe (35-39 weeks), we do not believe differences in placental leptin production were responsible for the differences in leptin concentration seen between normal weight and overweight/obese pregnant women.…”
Section: Discussionmentioning
confidence: 80%
“…Human studies suggest that preeclamptic patients express exaggerated metabolic profiles, including hyperleptinemia, hyperinsulinemia, insulin resistance, and hyperlipidemia, which precedes the appearance of the clinical symptoms (25,38,100,169). Intriguingly, in vitro and in vivo studies have shown that depending on the concentration of obesity-related metabolic factors, there are beneficial or detrimental effects on placentalfetal development and vascular function (33,62). We and others (146) believe that obese pregnant women having an extremely abnormal metabolic profile are at increased risk to develop PE.…”
Section: Effects Of Obesity On Placental Ischemia-induced Endothelialmentioning
confidence: 99%
“…Chez la femme, les concentrations sériques de plusieurs adipocytokines, comme la leptine [46,47], la visfatine [46], la résistine [46,47], ainsi que celle du TNF- [47], sont plus élevées en fin de grossesse, alors que les taux d'adiponectine circulante [46,47] sont diminués. De la même manière, la concentration de chémérine augmente au cours de la grossesse chez la femme, contrairement à ce hyperinsulinémie prolongée provoque une augmentation de la concentration de chémérine chez des individus sains [36].…”
Section: Chémérine Et Physiologie Foeto-maternelleunclassified